Preparation and Characterization of Psf-Based Ultrafiltration Membrane for Possible Filtration of Coconut Milk - Abdul Sukor, Nur Fatin Izzati; Basri, Hatijah; Atqiya Muslihati (Enhanced Knowledge in Sciences and Technology, 2021)
The membrane fabrication of polysulfone (Psf) was prepared via phase inversion method that using N-methyl-2- pyrroidone (NMP) as a solvent and polyethylene glycol (PEG) as an additive. The added PEG to the casting solution was differed in composition. The prepared membrane was characterized based on it mean pore size and SEM images. It is also subjected to the performance of flux by measuring pure water flux and PEG 20 kDA flux. All the prepared membrane indicates it is an ultrafiltration membrane based through average mean pore size obtained. The addition of PEG into Psf-based membrane increase it membrane permeability and enhance finger-like structure on membrane. The result also demonstrated, the PWF of pure water increased by 91% at PEG content 16 wt. % while PWF of PEG 20 kDA increased by 74% of PEG content of 12 wt. %.